2020
DOI: 10.3389/fonc.2020.00070
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Potentiates the Effect of Chemotherapy in Metastatic Melanoma—A Retrospective Study

Abstract: Melanoma survival increased with targeted-and immunotherapy agents, yet most patients ultimately progress and require salvage therapy. In our experience, some progressive disease patients on immune-checkpoint inhibitors (ICIs) demonstrate deep and sustained responses to chemotherapy. We hypothesized that ICIs improve the response to subsequent chemotherapy in metastatic melanoma. We conducted a retrospective study to compare the efficacy of chemotherapy given with prior immunotherapy, to its efficacy given wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 25 publications
2
27
0
10
Order By: Relevance
“…Median PFS was significantly longer in the group receiving chemotherapy after immunotherapy (respectively 5.2 vs 2.5 months, P = .046). [ 11 ] Another Japanese retrospective study of 9 patients treated with chemotherapy after immunotherapy showed comparable outcome results (mean PFS 5.0 months and mean OS 7.6 months). [ 12 ] Several hypotheses can be advanced to explain this better prognosis, including selection bias of long-responder patients, or continuation of the immunotherapy effect after its discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…Median PFS was significantly longer in the group receiving chemotherapy after immunotherapy (respectively 5.2 vs 2.5 months, P = .046). [ 11 ] Another Japanese retrospective study of 9 patients treated with chemotherapy after immunotherapy showed comparable outcome results (mean PFS 5.0 months and mean OS 7.6 months). [ 12 ] Several hypotheses can be advanced to explain this better prognosis, including selection bias of long-responder patients, or continuation of the immunotherapy effect after its discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in a multicenter retrospective study of R/M HNSCC, a taxane-based regimen after ICI was associated with higher ORR than other chemotherapy regimens (53 vs. 25%, p = 0.024) ( 35 ). Also, according to a retrospective study of metastatic melanoma, an increased proportion of CD8-positive cells with elevated PD-1 and CD69 expression was observed while on chemotherapy as compared with all-time points on ICIs, suggesting immune-activation by interaction of chemotherapy and ICIs ( 36 ). For R/M HNSCC, pembrolizumab or pembrolizumab+platinum+5FU showed significantly better OS than the EXTREME regimen and became a standard first-line treatment ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, since cetuximab remains a key chemotherapy drug for R/M SCCHN, it is expected that cetuximab is increasingly used as a second- or later-line setting after exposure to immunotherapy. Several studies have demonstrated potential improvements in the treatment outcomes of cytotoxic chemotherapy after exposure to immunotherapy in various types of malignancies, including malignant melanoma, non-small cell lung cancer and stomach cancer [ 7 9 ]. In R/M SCCHN, two retrospective studies assessed patients who progressed on ICIs and subsequently underwent cytotoxic chemotherapy; these studies reported a relatively higher overall response rate (ORR) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%